Digitalisasi Akuntansi untuk UMKM Sociopreneur: Meningkatkan Transparansi dan Keberlanjutan Keuangan - Salsabila, Gita Ayu Salsabila; Sriwindari, Asti; Rahmawati, Nurul Alfida (Universitas Pamulang, 2025)
This research examines the role of accounting digitalization in improving the transparency and financial sustainability of sociopreneur MSMEs through community service and increasing financial literacy. By adopting digital technology in financial recording and reporting, sociopreneur MSMEs can manage finances more accurately, efficiently and transparently, The methods used in this community service (abdimisi) activity are extension (or outreach/counseling) and participatory consultation. thus supporting better decision-making and business sustainability. Financial literacy training as part of community service is proven to increase the understanding and ability of MSME actors to implement accounting digitalization, which has a positive impact on financial performance and business competitiveness. These findings confirm the importance of integrating accounting digitalization and financial literacy to strengthen prospective sociopreneur MSMEs in facing modern economic challenges. Keywords: Community Service; MSMEs; Sociopreneur